2014
DOI: 10.1542/peds.2014-0780
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ Best Interests in End-of-life Care for Newborns

Abstract: BACKGROUND AND OBJECTIVES: Pediatric bioethics presumes that decisions should be taken in the child’s best interest. If it’s ambiguous whether a decision is in the child's interest, we defer to parents. Should parents be permitted to consider their own interests in making decisions for their child? In the Netherlands, where neonatal euthanasia is legal, such questions sometimes arise in deciding whether to hasten the death of a critically ill, suffering child. We describe the recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 23 publications
1
21
1
6
Order By: Relevance
“…In other words, the respondents agreed more with using conservative, rather than active, interventions in relation to end-of-life decision making about dying neonates; these results are similar to the findings obtained from studies conducted in other Asian countries 9,11) . In contrast, our results differ from those obtained from studies conducted in European countries, where many doctors agreed with using active interventions, such as withdrawal of mechanical ventilation 8,[12][13][14][15] . Interestingly, the respondents agreed most with active interventions required for reducing pain (80%); this differs from findings of other studies conducted in Asian countries but is similar to the high agreement rate observed in European studies 4,8,15) .…”
Section: Discussioncontrasting
confidence: 99%
“…In other words, the respondents agreed more with using conservative, rather than active, interventions in relation to end-of-life decision making about dying neonates; these results are similar to the findings obtained from studies conducted in other Asian countries 9,11) . In contrast, our results differ from those obtained from studies conducted in European countries, where many doctors agreed with using active interventions, such as withdrawal of mechanical ventilation 8,[12][13][14][15] . Interestingly, the respondents agreed most with active interventions required for reducing pain (80%); this differs from findings of other studies conducted in Asian countries but is similar to the high agreement rate observed in European studies 4,8,15) .…”
Section: Discussioncontrasting
confidence: 99%
“…According to the expert committee's definition of deliberately ending life, this act would classify as such and should be reported 3. The KNMG also states this act should be reported as deliberately ending life, but they disagree with the expert committee about how it should be reviewed 12. The physician in case 1, however, classified this death as a ‘natural’ death and did not report it to the committee.…”
Section: Discussionmentioning
confidence: 99%
“…Life-shortening drugs to hasten death might then be used to end a protracted dying process 10 11. Recently, the Royal Dutch Medical Association (KNMG) has published a report with recommendations on end-of-life decisions for newborns, in which they express the opinion that the use of lethal drugs (ie, neuromuscular blockers) to end a protracted dying process (whether to relieve the suffering of the patient or the parents) should be seen as acceptable 12. According to the KNMG, this act should be reported to the expert committee who should review it as acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…25 A study in the Netherlands suggested that treatment should generally be considered conditional and if the treatment fails, it can be abandoned. 26 It is noted that for all healthcare providers who have the decisive role in end of life decisions, euthanasia and decision making on the provision of care can create serious ethical problems 27 that needs to be discussed with more details in future studies.…”
Section: Disscusionmentioning
confidence: 99%